Japanese in 10 minutes a day - Kershul, Kristine (Bilingual Books, 1982)
The book walks you through your language in 23 easy steps. Almost automatically you will acquire a large working vocabulary that will suit your needs. As you work through the steps, use the sticky labels (included). At the back of the book, you will also find cut-out flash cards to make learning fun. When you have completed the book, cut out the menu at the back and take it along on your trip. Available in 11 languages